Hubungan Antara Dukungan Sosial dengan Culture Shock pada Santri Putri Baru di Pondok Pesantren - Salwa Alya Azzahra; Wahyu Endang Setyowati; Betie Febriana (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Most students who have just arrived and live in a new area experience culture shock. This is because it is difficult to adapt and adjust to their social life. Social support is very important to be given especially to new students, because social support can provide comfort and a feeling of being loved. Method: Quantitative research type with cross sectional approach. The sample used was 100 students in Lasem with the technique used was total sampling. The correlation test used in this study was the Chi-square test. The results of the study showed that the majority of students had good social support with moderate culture shock, namely 58 students (58%). Based on the Chi-square test, a p-value of 0.000 (<0.05) was obtained, which means that there is a relationship between social support and culture shock in students at Islamic Boarding Schools in Lasem. There is a close relationship between social support and culture shock in students in Lasem (p value 0.000).